Road to Recovery: Understanding the Personality Typology, Clinical Features, and Risk of Relapse in Filipinos with Substance Use Problems - Ronquillo, Marc Angelo; Reyes, Marc Eric; Cayubit, Ryan Francis (UI Scholars Hub, 2025)
Knowing the patient’s personality can assist the clinician in improving their relationship and tailoring the interventions for the patient. Several studies have reported that treatment and prevention programs must be tailored to an individual’s social and cultural attributes to facilitate continuous recovery and prevent relapse. This study aimed to develop a deeper understanding of the personality typology, clinical features, and risk of relapse in Filipinos with substance use problems in rehabilitation centers. We used a sequential-explanatory mixed-method approach with two phases (Phase 1: descriptive, cross-sectional design; Phase 2: phenomenological design) to provide an evidence-based framework to tailor treatment according to the personality of individuals with substance use problems. Phase 1 results revealed only one personality cluster for Filipinos with substance use problems, i.e., neurotic-extravert. Participants also had high scores on different scales in the MCMI-III and displayed high chances of reusing illicit substances. Phase 2 revealed four themes: avoidance coping, unwillingness to change, preference for social activities, and perceived lack of support. Integrating the findings of our two phases led to the development of the proposed treatment framework for Filipinos with substance use problems, including activities focused on developing positive coping mechanisms, increasing the motivation of Filipinos with substance use problems, having social activities, fostering support systems, and a post-treatment program. Our study’s findings may aid mental health professionals engaged in substance use prevention and recovery in creating better treatment programs and reducing posttreatment relapse tendencies.